Metacognitive Strategy : Optimalization Generic Skills Through E-Accounting Materials - Sumaryati, Sri (Sebelas Maret University, 2016)
Educational research and practice strongly supports the notion of general cognitive skills instruction. High quality instruction enables students of all ages to construct domain specific and domain-general strategies, metacognitive knowledge about themselves and their cognitive skills, and how to better regulate their cognition. The starting point in this endeavor is for teachers (or expert students) to ask themselves what skills and strategies are important within the specific domain they teach, how they constructed these skills within their own repertoire of cognitive skills, and what they can tell their students about using these skills intelligently. The purpose of this article is to offer a strategy that is able to integrate the value of generic skills through integrated teaching materials based metacognitive strategy, which is able to accommodate the needs of students in recognizing its accuracy in learning so that the learning process can be carried out effectively and efficiently. This article was written based on a review of the relevant literature. The article concludes that the value of generic skills can be developed through the use of teaching materials that allow learners to develop generic skills that are needed in the course of his life